Model Driven Testing based on Functional Test Case Generation with Redundancy Check - Farooq, Aadil; Jadhav, Pramod; Joshi, SD (International Journal of Computer Sciences and Engineering, 2019)
Software testing is a major component of software development lifecycle and it’s time-consuming. The testing used the particular time in testing is generally disturbed with generating the test cases and correctly testing them. Although some people apply k-means clustering algorithm to the test suite reduction, the algorithm is unstable and seldom considers the coverage rate of such test cases; as a result, it will waste various unnecessary testing times in redundant cases and always result in high cost. Model-based testing method is one of the testing categories in which the test cases derived from that the system describes efficient aspects of the system under test. When the model of the system is described explicitly, reversing system performed correctly, it can be used for the renewable artifact. For instance, the system can be used to generate an appropriate test set for the SUT. Such technique is called model-based testing (MBT).The different approaches are implemented and evaluated in order to determine its effectiveness in reducing the redundancy of test case generation. The purpose of this project is to generate the test cases, prioritize them.